2011
DOI: 10.1007/s10584-011-0241-3
|View full text |Cite
|
Sign up to set email alerts
|

Adapting California’s water management to climate change

Abstract: California faces significant water management challenges from climate change, affecting water supply, aquatic ecosystems, and flood risks. Fortunately, the state also possesses adaptation tools and institutional capabilities that can limit vulnerability to changing conditions. Water supply managers have begun using underground storage, water transfers, conservation, recycling, and desalination to meet changing demands. These same tools are promising options for responding to a wide range of climate changes. Li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
104
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(110 citation statements)
references
References 44 publications
1
104
0
1
Order By: Relevance
“…Climate change adaptation has received growing attention as an important response strategy and management option to reduce vulnerability and enhance resilience in different sectors, including water resources (Connell-Buck et al 2011;Charlton and Arnell 2011;Sowers et al 2011;Hanak and Lund 2012;Iglesias et al 2013), agriculture (Reidsma et al 2010;Olesen et al 2011;Klein et al 2013), energy (Madani and Lund 2010;Guegan et al 2012;Jamali et al 2013;Madani et al 2014) and environment (Palmer et al 2009;Cross et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Climate change adaptation has received growing attention as an important response strategy and management option to reduce vulnerability and enhance resilience in different sectors, including water resources (Connell-Buck et al 2011;Charlton and Arnell 2011;Sowers et al 2011;Hanak and Lund 2012;Iglesias et al 2013), agriculture (Reidsma et al 2010;Olesen et al 2011;Klein et al 2013), energy (Madani and Lund 2010;Guegan et al 2012;Jamali et al 2013;Madani et al 2014) and environment (Palmer et al 2009;Cross et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…An increased relative water scarcity, together with higher levels of salinity, makes rise conflicts and competition among users over the allocation of water (Rijsberman 2006). The literature review and the findings of this study suggest that higher temperatures are also expected to change water demands and have direct physical effects on the plant growth and development (IPCC 2013, Hanak andLund 2012). Pulido-Calvo et al (2012) found that in dry periods a mean temperature increase of 1°C in low altitude locations of the Guadalquivir River Basin will result in a mean increase of 12 % in the irrigation demand on outflows.…”
Section: The View Of Local Communities: Main Risks and Local Adaptatimentioning
confidence: 84%
“…The critical importance of institutional good governance has been previously established as a requirement for the regional adaptation capacity by preceding research (Berrang-Ford et al 2014;Hanak and Lund 2012;Iglesias 2009). Increase scientific research, farmer training and technical advice were governance options perceived positively by all the groups.…”
Section: Towards Adaptation To Climate Changementioning
confidence: 99%
See 1 more Smart Citation
“…The statistical tool presented in this work, relating NPH anomaly to precipitation or snowpack indices, can be applied to other California watersheds, where it may allow reservoir operators additional insight, on a year-to-year basis, on whether some of the flood storage could be utilized for water supply storage. This additional insight could be of great value in coming decades, where operators must make the most from a potentially more variable precipitation season, as well as declining snowpack due to higher temperatures and a partial shift from snowfall to rainfall, and greater peaks in runoff in wet years (Fissekis, 2008;Brekke et al, 2009;Hanak and Lund, 2012).…”
Section: Wider Significance Of This Work and Future Researchmentioning
confidence: 99%